Long-Distance Imported Pottery at Horvat Kur (Galilee, Israel): Categories and Quantities - Bes, Philip (Rei Cretariae Romanae Fautorum Acta, 2020)
This paper presents data and preliminary observations concerning Roman, particularly Late Roman, pottery from the excavation of a synagogue at Horvat Kur, near Capernaum (Lower Galilee, Israel). Following introductory paragraphs concerning the site and the study of the pottery, the specific focus is on the categories of long-distance imported pottery that were identified amongst what is a ceramic assemblage of largely regional manufacture. Most notable is the relatively common presence of Pontic amphorae, very likely from the area of Sinope, and African Red Slip Ware, Late Roman C and D. The limited variety and quantity of this imported pottery serves as a basis to make preliminary observations concerning the significance of this pottery, as a reflection of a changing Mediterranean world on the macro scale, and local circumstances on the micro level.